From ultra-depleted harzburgite to refertilized lherzolite: Multi-stage metasomatism and crustal recycling recorded by garnet populations from the Newlands Kimberlite, South Africa - C. Bonadiman; L. Milani; R. Tassinari; N. Lenhardt; P.W.J. Delport; L. Rowe (Lithos, 2026)

Late Cretaceous paleoenvironments in the Mesopotamian Foreland Basin, northern Arabia: Petrographical, mineralogical, and geochemical evidence from the boundary of the Kometan and Shiranish Formations - Zaman R. Sherwani; Sarmad A. Ali; Ali I. Al-Juboury; Harry Rowe; Giovanni Zanoni; Ahmed M. Abdelhameed; Nagham Omar; Nasir Alarifi (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Mechanical and hydraulic behaviour of overlapped geosynthetic clay liners under differential settlement - Felix Y.H. Fan; R. Kerry Rowe (Geotextiles and Geomembranes, 2026)

A probabilistic evaluation of PFOS contamination of aquifers under municipal waste landfills with a single composite liner - Linxue Zhao; R. Kerry Rowe; Abbas El-Zein (Computers and Geotechnics, 2026)

Effects of secondary hydrothermal fluids on gallium distribution and coordination in hot springs silica using Ga K-edge XANES - M.C. Rowe; K.A. Campbell; D.A. Stallard; B. Lyon; A. Langendam; E. Kalinina; M. Yamanaka; R. Tanaka; T. Christopher; S.W. Ruff; E. Nersezova; T. Ota; et al. (Applied Geochemistry, 2026)

Leakage through waste covers with small geomembrane wrinkles - Felix Y.H. Fan; R. Kerry Rowe; Richard W.I. Brachman; J. Van Gulck (Geotextiles and Geomembranes, 2026)

Effect of aqueous ammonia, PFAS, and landfill leachate on antioxidant depletion from two high-density polyethylene geomembranes - M. Somuah; R. Kerry Rowe (Waste Management, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Cold temperature behaviour of polyethylene geomembranes - M. Somuah; F.B. Abdelaal; R. Kerry Rowe (Geotextiles and Geomembranes, 2026)

Impact of diagenesis and acidic alteration on microbial fabrics and trace element distributions in fossilised siliceous hot spring deposits - Barbara J. Lyon; Michael C. Rowe; Andrew Langendam; Kathleen A. Campbell; Diego M. Guido; Ayrton R. Hamilton; Ema E. Nersezova; Amanda Galar; Dominique A. Stallard (Geochimica et Cosmochimica Acta, 2026)

Estimating mercury exposure in amphibians using non-lethal tissue sampling - Caitlin T. Rumrill; Kelly L. Smalling; Colleen Emery; Blake R. Hossack; Brian J. Halstead; Michael J. Adams; Adam R. Backlin; Adrianne B. Brand; Jon M. Davenport; Robert N. Fisher; Jill Fleming; Brad M. Glorioso; et al. (Ecotoxicology, 2026)

Assessing methane production and feed efficiency in both growing and mature ovine animals in six countries across Europe, South America and Oceania - Fiona.M. McGovern; Patricia L. Johnson; Noirin McHugh; Flavie Tortereau; Christel Marie-Etancelin; Elly A. Navajas; Ignacio De Barbieri; Bente Aspeholen Åby; Suzanne J. Rowe; Joanne Conington; Gabriel Ciappesoni; Ingjerd Dønnem; et al. (Small Ruminant Research, 2026)

Honey bee beards: internal and external factors driving mass thermoregulatory evacuation - E. B. Rowe; P. Prathibha; P. R. Marting; M. L. Smith (Insectes Sociaux, 2026)
Honeybees are master thermoregulators, capable of maintaining nest homeostasis across fluctuating ambient temperatures. When workers must cool their nest, they use multiple thermoregulatory behaviors (e.g., fanning, collecting water), but bearding, where hundreds to thousands of workers evacuate their nest and form a bivouac outside, is relatively unexplored. Here, we (1) describe natural bearding patterns, (2) experimentally manipulate colonies to determine what impacts beard size and timing, and (3) explore how workers dissipate back into their nest. We show that bearding occurs daily in hot weather, but the largest beards consistently happen in the evening/night, between the hours of 1800 and 2400. Beards are located around the nest entrance, but workers bias their position toward the shaded side of the nest box. As colony size increases, beard size and duration also increase, but the proportion of the colony bearding does not increase with colony size. Colonies with and without brood still cast beards; brood presence/absence did not impact beard size or duration. After noticing that beards tend to dissipate at sunrise, we experimentally showed that beards induced in the afternoon dissipate within 1–2 h, whereas beards induced in the evening remain overnight (10+ h). Bearding overnight, however, does carry risks for developing brood inside, as nest temperatures dropped below the optimal range, until the beard dissipated at sunrise. What cues workers use to depart the beard remain unknown, but experimentally illuminating colonies at night did not induce beards to dissipate. Our results suggest that bearding is an individual decision, not one that is coordinated across the colony. Still, these individual actions result in a dramatic collective response that colonies employ to reduce the temperature of their nest. Here, we show how and when colonies use bearding, despite its risks.

Degradation of polyethylene geomembranes exposed to different mine tailings pore waters - Rodrigo A. e Silva; R. Kerry Rowe; Fady B. Abdelaal (Geotextiles and Geomembranes, 2025)

Life and death of a sinter archive: Evolution of siliceous hot-spring deposits (Holocene) on the dynamic Paeroa Fault at Te Kopia, Taupō Volcanic Zone, New Zealand - M.C. Rowe; K.A. Campbell; A. Hamilton; Y. Jiang; J. Pelser; B. Murphy; R. Martin; K.M. Mackenzie; D.A. Stallard; B. Lyon; A. Langendam; E.E. Nersezova; et al. (Journal of Volcanology and Geothermal Research, 2025)

The effect of a bench on leakage through a cover: A field and numerical assessment - Felix Y.H. Fan; R. Kerry Rowe; R.W.I. Brachman; Jamie F. VanGulck (Geotextiles and Geomembranes, 2025)

Initial hydration characteristics of dry montmorillonite and insights for water transport mechanisms in nanochannels - Bonan Li; Chengkai Li; Yilin Gui; Haifei Zhan; Yuantong Gu; Miao Yu; R. Kerry Rowe (Computers and Geotechnics, 2025)

Systemic deficits in lipid homeostasis promote aging-associated impairments in B cell progenitor development - Silvia Vicenzi; Fangyuan Gao; Parker Côté; Joshua D. Hartman; Lara C. Avsharian; Ashni A. Vora; R. Grant Rowe; Hojun Li; Dorota Skowronska-Krawczyk; Leslie A. Crews (GeroScience, 2025)
Organismal aging has been associated with diverse metabolic and functional changes across tissues. Within the immune system, key features of physiological hematopoietic cell aging include increased fat deposition in the bone marrow, impaired hematopoietic stem and progenitor cell (HSPC) function, and a propensity towards myeloid differentiation. This shift in lineage bias can lead to pre-malignant bone marrow conditions such as clonal hematopoiesis of indeterminate potential (CHIP) or clonal cytopenias of undetermined significance (CCUS), frequently setting the stage for subsequent development of age-related cancers in myeloid or lymphoid lineages. Human aging has also been associated with diverse lipid alterations across tissues, such as decreased phospholipid membrane fluidity that arises as a result of increased saturated fatty acid (FA) accumulation and a decay in n-3 polyunsaturated fatty acid (PUFA) species by the age of 80 years, however the extent to which impaired FA metabolism contributes to hematopoietic aging is less clear. Here, comprehensive multi-omics analyses uncovered a role for a key PUFA biosynthesis gene, ELOVL2 , in mouse and human immune cell aging. Whole transcriptome RNA-sequencing studies and complementary flow cytometric analyses of bone marrow from aged Elovl2 mutant (enzyme-deficient) mice compared with age-matched controls revealed global downregulation in lymphoid cell markers and expression of genes involved specifically in B cell development. These studies unveiled CD79B, a vital molecular regulator of lymphoid progenitor development from the pro-B to pre-B cell stage, as a putative surface biomarker whose loss is associated with accelerated immune aging. The lipidome of mutant versus wild-type mice also displayed significant changes in the biophysical properties of cellular membranes. To investigate the relevance of these finding to human bone marrow aging, analyses of a single cell RNA-seq dataset of human HSPCs across the spectrum of human development and aging uncovered a rare subpopulation (< 7%) of CD34 + HSPCs that expresses ELOVL2 in healthy adult bone marrow. This HSPC subset, along with CD79B -expressing lymphoid-committed cells, were almost completely absent in CD34 + cells isolated from elderly bone marrow samples. Together, these findings uncover new roles for lipid metabolism enzymes in the molecular regulation of cellular aging and immune cell function in mouse and human hematopoiesis. In addition, because systemic loss of ELOVL2 enzymatic activity resulted in downregulation of B cell genes that are also associated with lymphoproliferative neoplasms, this study sheds light on an intriguing metabolic pathway that could be leveraged in future studies as a novel therapeutic modality to target blood cancers or other age-related conditions involving the B cell lineage.

Long-term performance of polyethylene geomembranes to contain brine - M. Zafari; R. Kerry Rowe; R. Awad (Geotextiles and Geomembranes, 2025)

Knowledge, perception and ownership by local stakeholders among the world’s largest shark sanctuary a decade after its inception - Clémentine JM Séguigne; Mark E. Bond; Adeline Goyaud; Michael R. Heithaus; Gilles Siu; Zenya Rowe; Frédéric Torrente; Eric Clua (Marine Policy, 2025)

Resolving Symbiodiniaceae Diversity Across Coral Microhabitats and Reef Niches - Wyatt C. Million; Christian R. Voolstra; Gabriela Perna; Giulia Puntin; Katherine Rowe; Maren Ziegler (Environmental Microbiology, 2025)
Dinoflagellates of the family Symbiodiniaceae are important symbionts of diverse marine animals and they also occupy different environmental niches on coral reefs. The link between diversity at ecosystem‐scale to microhabitats of Symbiodiniaceae within the coral holobiont is largely unknown. Using ITS2‐amplicon sequencing, we compared Symbiodiniaceae communities across four environments (seawater, near‐reef vs. distant sediments and turf algae) and two coral microhabitats (tissue, mucus) on a coral reef in the Red Sea. We found that coral and environmental habitats were both dominated by the genera Symbiodinium , Cladocopium and Durusdinium , but environmental habitats additionally harboured Fugacium , Gerakladium and Halluxium . Each environmental habitat harboured a distinct Symbiodiniaceae community. Nonetheless, 17 ITS2 sequences were shared among coral and environmental habitats and were also part of nearly half of the ITS2 type profiles in coral‐based communities. Tissues and mucus of 49 coral colonies from 17 genera had largely identical Symbiodiniaceae communities. Together with the large difference between environmental Symbiodiniaceae communities and those in the coral tissue and mucus, our results indicate a clear barrier between host‐associated and environmental Symbiodiniaceae communities marked by only few shared complete type profiles. Monitoring coral colonies after mucus sampling confirmed its suitability for long‐term monitoring of coral‐associated Symbiodiniaceae communities.

Effect of backfilling surface settlement trough on waste cover leakage - Felix Y.H. Fan; R. Kerry Rowe; Richard W.I. Brachman; Jamie F. VanGulck (Geotextiles and Geomembranes, 2025)

A 9-year study of the degradation of a HDPE geomembrane liner used in different high pH mining applications - Rodrigo A. e Silva; Fady B. Abdelaal; R. Kerry Rowe (Geotextiles and Geomembranes, 2025)

Implications of single and double liners on the impact of PFOA in landfills on an underlying aquifer - Farah B. Barakat; R. Kerry Rowe (Geotextiles and Geomembranes, 2025)

The Genomic Signature and Transcriptional Response of Metal Tolerance in Brown Trout Inhabiting Metal‐Polluted Rivers - Josephine R. Paris; R. Andrew King; Joan Ferrer Obiol; Sophie Shaw; Anke Lange; Vincent Bourret; Patrick B. Hamilton; Darren Rowe; Lauren V. Laing; Audrey Farbos; Karen Moore; Mauricio A. Urbina; et al. (Molecular Ecology, 2025)
Industrial pollution is a major driver of ecosystem degradation, but it can also act as a driver of contemporary evolution. As a result of intense mining activity during the Industrial Revolution, several rivers across the southwest of England are polluted with high concentrations of metals. Despite the documented negative impacts of ongoing metal pollution, brown trout ( Salmo trutta L.) survive and thrive in many of these metal‐impacted rivers. We used population genomics, transcriptomics, and metal burdens to investigate the genomic and transcriptomic signatures of potential metal tolerance. RADseq analysis of six populations (originating from three metal‐impacted and three control rivers) revealed strong genetic substructuring between impacted and control populations. We identified selection signatures at 122 loci, including genes related to metal homeostasis and oxidative stress. Trout sampled from metal‐impacted rivers exhibited significantly higher tissue concentrations of cadmium, copper, nickel and zinc, which remained elevated after 11 days in metal‐free water. After depuration, we used RNAseq to quantify gene expression differences between metal‐impacted and control trout, identifying 2042 differentially expressed genes (DEGs) in the gill, and 311 DEGs in the liver. Transcriptomic signatures in the gill were enriched for genes involved in ion transport processes, metal homeostasis, oxidative stress, hypoxia, and response to xenobiotics. Our findings reveal shared genomic and transcriptomic pathways involved in detoxification, oxidative stress responses and ion regulation. Overall, our results demonstrate the diverse effects of metal pollution in shaping both neutral and adaptive genetic variation, whilst also highlighting the potential role of constitutive gene expression in promoting metal tolerance.

Creep rupture behaviour of elastomeric bituminous geomembrane seams - Jiying Fan; R. Kerry Rowe (Geotextiles and Geomembranes, 2024)

Taxonomic and environmental significance of Poaceae and Cyperaceae phytoliths from the Northern Territory, Australia - Kelsey C. Boyd; Carlos E. Cordova; Haidee R. Cadd; Cassandra Rowe; Tim J. Cohen (Review of Palaeobotany and Palynology, 2024)

Woody plant phytolith morphology and representation in surface sediments across the Northern Territory, Australia - Kelsey C. Boyd; Carlos E. Cordova; Haidee R. Cadd; Cassandra Rowe; Tim J. Cohen (Review of Palaeobotany and Palynology, 2024)

Intertidal seagrass extent from Sentinel-2 time-series show distinct trajectories in Western Europe - Bede Ffinian Rowe Davies; Simon Oiry; Philippe Rosa; Maria Laura Zoffoli; Ana I. Sousa; Oliver R. Thomas; Dan A. Smale; Melanie C. Austen; Lauren Biermann; Martin J. Attrill; Alejandro Roman; Gabriel Navarro; et al. (Remote Sensing of Environment, 2024)

Traumatic Brain Injury in Mice Generates Early-Stage Alzheimer’s Disease Related Protein Pathology that Correlates with Neurobehavioral Deficits - Nicholas Panayi; Philip Schulz; Ping He; Brandon Hanna; Jonathan Lifshitz; Rachel K. Rowe; Michael R. Sierks (Molecular Neurobiology, 2024)
Traumatic brain injury (TBI) increases the long-term risk of neurodegenerative diseases, including Alzheimer’s disease (AD). Here, we demonstrate that protein variant pathology generated in brain tissue of an experimental TBI mouse model is similar to protein variant pathology observed during early stages of AD, and that subacute accumulation of AD associated variants of amyloid beta (Aβ) and tau in the TBI mouse model correlated with behavioral deficits. Male C57BL/6 mice were subjected to midline fluid percussion injury or to sham injury, after which sensorimotor function (rotarod, neurological severity score), cognitive deficit (novel object recognition), and affective deficits (elevated plus maze, forced swim task) were assessed post-injury (DPI). Protein pathology at 7, 14, and 28 DPI was measured in multiple brain regions using an immunostain panel of reagents selectively targeting different neurodegenerative disease-related variants of Aβ, tau, TDP-43, and alpha-synuclein. Overall, TBI resulted in sensorimotor deficits and accumulation of AD-related protein variant pathology near the impact site, both of which returned to sham levels by 14 DPI. Individual mice, however, showed persistent behavioral deficits and/or accumulation of toxic protein variants at 28 DPI. Behavioral outcomes of each mouse were correlated with levels of seven different protein variants in ten brain regions at specific DPI. Out of 21 significant correlations between protein variant levels and behavioral deficits, 18 were with variants of Aβ or tau. Correlations at 28 DPI were all between a single Aβ or tau variant, both of which are strongly associated with human AD cases. These data provide a direct mechanistic link between protein pathology resulting from TBI and the hallmarks of AD.

Transport parameters for PFOA and PFOS migration through GCL's and composite liners used in landfills - Farah B. Barakat; R. Kerry Rowe; David Patch; Kela Weber (Geotextiles and Geomembranes, 2024)

Using strain hardening to predict the stress crack resistance of unaged and aged smooth black HDPE geomembranes - M. Ali; R. Kerry Rowe; F.B. Abdelaal (Geotextiles and Geomembranes, 2024)

Effect of a lateral drainage layer on leakage through a defect in a geomembrane overlain by saturated tailings - Jiying Fan; R. Kerry Rowe (Geotextiles and Geomembranes, 2024)

Effect of welding parameters on properties of HDPE geomembrane extrusion welds - R. Kerry Rowe; M. Mouhamed Ali (Geotextiles and Geomembranes, 2024)

Early Aboriginal pottery production and offshore island occupation on Jiigurru (Lizard Island group), Great Barrier Reef, Australia - Sean Ulm; Ian J. McNiven; Glenn R. Summerhayes; Pei-hua Wu; Magdalena M.E. Bunbury; Fiona Petchey; Quan Hua; Robert Skelly; Ariana B.J. Lambrides; Cassandra Rowe; Kelsey M. Lowe; Christian H. Reepmeyer; et al. (Quaternary Science Reviews, 2024)

Long-term durability of two HDPE geomembranes formulated with polyethylene of raised temperature resistance (PE-RT) - Matthew Clinton; R. Kerry Rowe (Geotextiles and Geomembranes, 2024)

Understanding structural anisotropy and mechanical properties of Na-montmorillonite with crystalline swelling and uniaxial deformation under different hydration degrees - Bonan Li; Chengkai Li; Yilin Gui; Haifei Zhan; Yuantong Gu; Miao Yu; R. Kerry Rowe (Computers and Geotechnics, 2024)

Utility of wastewater genomic surveillance compared to clinical surveillance to track the spread of the SARS-CoV-2 Omicron variant across England - Franziska S. Brunner; Alexander Payne; Edward Cairns; George Airey; Richard Gregory; Natalie D. Pickwell; Myles Wilson; Matthew Carlile; Nadine Holmes; Verity Hill; Harry Child; Jasmine Tomlinson; et al. (Water Research, 2023)

Degradation of HDPE, LLDPE, and blended polyethylene geomembranes in extremely low and high pH mining solutions at 85 °C - F.B. Abdelaal; R. Kerry Rowe; M.S. Morsy; R.A. e Silva (Geotextiles and Geomembranes, 2023)

The Management of Non-IgE-mediated Allergies in Human Milk Fed Infants - S. Rowe; H. Lima; A. Licata; J. Hoffman; R. Durban (Journal of the Academy of Nutrition and Dietetics, 2023)

Development of an advanced machine learning model to predict the pH of groundwater in permeable reactive barriers (PRBs) located in acidic terrain - Subhani Medawela; Danial Jahed Armaghani; Buddhima Indraratna; R. Kerry Rowe; Natalie Thamwattana (Computers and Geotechnics, 2023)

Long-term Performance of Conductive-backed multilayered HDPE Geomembranes - M. Zafari; F.B. Abdelaal; R. Kerry Rowe (Geotextiles and Geomembranes, 2023)

Effect of geosynthetic component characteristics on the potential for GCL internal erosion - Jiying Fan; R. Kerry Rowe (Geotextiles and Geomembranes, 2023)

PCB containment using geosynthetics in Canada's Arctic - Daniel D. Jones; Rebecca S. McWatters; R. Kerry Rowe; Indra Kalinovich; Allison Rutter (Polar Science, 2023)

The need to consider the service life of all components of a modern MSW landfill liner system - R. Kerry Rowe; J. Reinert; Y. Li; R. Awad (Waste Management, 2023)

Effect of subgrade on leakage through a defective geomembrane seam below saturated tailings - Jiying Fan; R. Kerry Rowe (Geotextiles and Geomembranes, 2023)

Effects of perfluoroalkyl substances (PFAS) on antioxidant depletion from a high-density polyethylene geomembrane - R. Kerry Rowe; M. Somuah (Journal of Environmental Management, 2023)

Importance of thickness reduction and squeeze-out Std-OIT loss for HDPE geomembrane fusion seams - William Francey; R. Kerry Rowe (Geotextiles and Geomembranes, 2023)

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Empirically derived thermal thresholds of four coral species along the Red Sea using a portable and standardized experimental approach - Nicolas R. Evensen; Christian R. Voolstra; Maoz Fine; Gabriela Perna; Carol Buitrago-López; Anny Cárdenas; Guilhem Banc-Prandi; Katherine Rowe; Daniel J. Barshis (Coral Reefs, 2022)
Global warming is causing an unprecedented loss of species and habitats worldwide. This is particularly apparent for tropical coral reefs, with an increasing number of reefs experiencing mass bleaching and mortality on an annual basis. As such, there is a growing need for a standardized experimental approach to rapidly assess the thermal limits of corals and predict the survival of coral species across reefs and regions. Using a portable experimental system, the Coral Bleaching Automated Stress System (CBASS), we conducted standardized 18 h acute thermal stress assays to quantitively determine the upper thermal limits of four coral species across the length of the Red Sea coastline, from the Gulf of Aqaba (GoA) to Djibouti (~ 2100 km). We measured dark-acclimated photosynthetic efficiency ( F v /F m ), algal symbiont density, chlorophyll a, and visual bleaching intensity following heat stress. F v /F m was the most precise response variable assessed, advancing the F v /F m effective dose 50 (ED50, i.e., the temperature at which 50% of the initial F v /F m is measured) as an empirically derived proxy for thermal tolerance. ED50 thermal thresholds from the central/southern Red Sea and Djibouti populations were consistently higher for Acropora hemprichii, Pocillopora verrucosa, and Stylophora pistillata (0.1–1.8 °C above GoA corals, respectively), in line with prevailing warmer maximum monthly means (MMMs), though were lower than GoA corals relative to site MMMs (1.5–3.0 °C). P. verrucosa had the lowest thresholds overall. Despite coming from the hottest site, thresholds were lowest for Porites lobata in the southern Red Sea, suggesting long-term physiological damage or ongoing recovery from a severe, prior bleaching event. Altogether, the CBASS resolved historical, taxonomic, and possibly recent environmental drivers of variation in coral thermal thresholds, highlighting the potential for a standardized, short-term thermal assay as a universal approach for assessing ecological and evolutionary variation in the upper thermal limits of corals.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Contrasting heat stress response patterns of coral holobionts across the Red Sea suggest distinct mechanisms of thermal tolerance - Christian R. Voolstra; Jacob J. Valenzuela; Serdar Turkarslan; Anny Cárdenas; Benjamin C. C. Hume; Gabriela Perna; Carol Buitrago‐López; Katherine Rowe; Monica V. Orellana; Nitin S. Baliga; Suman Paranjape; Guilhem Banc‐Prandi; et al. (Molecular Ecology, 2021)
Corals from the northern Red Sea, in particular the Gulf of Aqaba (GoA), have exceptionally high bleaching thresholds approaching >5℃ above their maximum monthly mean (MMM) temperatures. These elevated thresholds are thought to be due to historical selection, as corals passed through the warmer Southern Red Sea during recolonization from the Arabian Sea. To test this hypothesis, we determined thermal tolerance thresholds of GoA versus central Red Sea (CRS) Stylophora pistillata corals using multi‐temperature acute thermal stress assays to determine thermal thresholds. Relative thermal thresholds of GoA and CRS corals were indeed similar and exceptionally high (~7℃ above MMM). However, absolute thermal thresholds of CRS corals were on average 3℃ above those of GoA corals. To explore the molecular underpinnings, we determined gene expression and microbiome response of the coral holobiont. Transcriptomic responses differed markedly, with a strong response to the thermal stress in GoA corals and their symbiotic algae versus a remarkably muted response in CRS colonies. Concomitant to this, coral and algal genes showed temperature‐induced expression in GoA corals, while exhibiting fixed high expression (front‐loading) in CRS corals. Bacterial community composition of GoA corals changed dramatically under heat stress, whereas CRS corals displayed stable assemblages. We interpret the response of GoA corals as that of a resilient population approaching a tipping point in contrast to a pattern of consistently elevated thermal resistance in CRS corals that cannot further attune. Such response differences suggest distinct thermal tolerance mechanisms that may affect the response of coral populations to ocean warming.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Plant silicon application alters leaf alkaloid concentrations and impacts parasitoids more adversely than their aphid hosts - Casey R. Hall; Rhiannon C. Rowe; Meena Mikhael; Elizabeth Read; Sue E. Hartley; Scott N. Johnson (Oecologia, 2021)

Monitoring wetland water quality related to livestock grazing in amphibian habitats - Kelly L. Smalling; Jennifer C. Rowe; Christopher A. Pearl; Luke R. Iwanowicz; Carrie E. Givens; Chauncey W. Anderson; Brome McCreary; Michael J. Adams (Environmental Monitoring and Assessment, 2021)
Land use alteration such as livestock grazing can affect water quality in habitats of at-risk wildlife species. Data from managed wetlands are needed to understand levels of exposure for aquatic life stages and monitor grazing-related changes afield. We quantified spatial and temporal variation in water quality in wetlands occupied by threatened Oregon spotted frog ( Rana pretiosa ) at Klamath Marsh National Wildlife Refuge in Oregon, United States (US). We used analyses for censored data to evaluate the importance of habitat type and grazing history in predicting concentrations of nutrients, turbidity, fecal indicator bacteria (FIB; total coliforms, Escherichia coli ( E. coli ), and enterococci), and estrogenicity, an indicator of estrogenic activity. Nutrients (orthophosphate and ammonia) and enterococci varied over time and space, while E. coli , total coliforms, turbidity, and estrogenicity were more strongly associated with local livestock grazing metrics. Turbidity was correlated with several grazing-related constituents and may be particularly useful for monitoring water quality in landscapes with livestock use. Concentrations of orthophosphate and estrogenicity were elevated at several sites relative to published health benchmarks, and their potential effects on Rana pretiosa warrant further investigation. Our data provided an initial assessment of potential exposure of amphibians to grazing-related constituents in western US wetlands. Increased monitoring of surface water quality and amphibian population status in combination with controlled laboratory toxicity studies could help inform future research and targeted management strategies for wetlands with both grazing and amphibians of conservation concern.

Rural–urban disparities in colorectal cancer survival and risk among men in Utah: a statewide population-based study - Charles R. Rogers; Brenna E. Blackburn; Matthew Huntington; Karen Curtin; Roland J. Thorpe; Kerry Rowe; John Snyder; Vikrant Deshmukh; Michael Newman; Alison Fraser; Ken Smith; Mia Hashibe (Cancer Causes & Control, 2020)

Measuring sperm swimming performance in birds: effects of dilution, suspension medium, mechanical agitation, and sperm number - Emily R. A. Cramer; Melissah Rowe; Fabrice Eroukhmanoff; Jan T. Lifjeld; Glenn-Peter Sætre; Arild Johnsen (Journal of Ornithology, 2019)

Galápagos lava lizards (Microlophus bivittatus) respond dynamically to displays from interactive conspecific robots - David L. Clark; Joseph M. Macedonia; John W. Rowe; Michaela R. Austin; Isabella M. Centurione; Carlos A. Valle (Behavioral Ecology and Sociobiology, 2019)

Temperature influences on growth of unfished juvenile Northern cod ( Gadus morhua ) during stock collapse - Darrell R. J. Mullowney; George A. Rose; Earl G. Dawe; Sherrylynn Rowe; Gary L. Maillet; Eric J. Pedersen (Fisheries Oceanography, 2019)
This study examined growth of unfished juvenile Northern cod ( Gadus morhua ) off Newfoundland concomitant with stock collapse in the cold early 1990s. Two unpublished data sets were examined, one from collapse‐period trapping sites along the northeast coast of Newfoundland and one from a post‐collapse inshore trawl survey. Cumulative surface and bottom temperatures were significant predictors of growth rates of the young fish with year‐classes born during collapse experiencing slower growth than those born during subsequent warming. Relationships between accrued temperature and growth were consistent across periods, with slow growth of collapse‐period fish reflecting slower accumulation of temperature‐at‐age. Temperature influences were spatially broad‐based with no significant differences in growth rates for fish captured along the entire northeast coast of Newfoundland. Predicted differences in growth rates for collapse versus recovery year‐classes were proportional to cumulative surface temperatures but not cumulative bottom temperatures. Although significant, temperature effects on growth were relatively unimportant at youngest ages. Overall, growth differences between periods were small but large differences occurred between slowest and fastest growing year‐classes. The results suggest initial responses to increasing temperatures were delayed following collapse. We conclude that although temperature was an important determinant of dampened productivity that it alone cannot account for the collapse and slow recovery of the stock. This is the first known study to directly quantitatively link temperature impacts to an unfished component of the Northern cod stock complex during collapse, removing need for implicit assumptions about whether or not cold conditions contributed to the collapse of this iconic fish stock.

SMART Cables for Observing the Global Ocean: Science and Implementation - Bruce M. Howe; Brian K. Arbic; Jérome Aucan; Christopher R. Barnes; Nigel Bayliff; Nathan Becker; Rhett Butler; Laurie Doyle; Shane Elipot; Gregory C. Johnson; Felix Landerer; Stephen Lentz; et al. (Frontiers in Marine Science, 2019)

Gait stability in response to platform, belt, and sensory perturbations in young and older adults - S. Roeles; P. J. Rowe; S. M. Bruijn; C. R. Childs; G. D. Tarfali; F. Steenbrink; M. Pijnappels (Medical & Biological Engineering & Computing, 2018)

Variation in electrode redox potential selects for different microorganisms under cathodic current flow from electrodes in marine sediments - Bonita R. Lam; Annette R. Rowe; Kenneth H. Nealson (Environmental Microbiology, 2018)
Summary Extracellular electron transport (EET) is a microbial process that allows microorganisms to transport electrons to and from insoluble substrates outside of the cell. Although progress has been made in understanding how microbes transfer electrons to insoluble substrates, the process of receiving electrons has largely remained unexplored. We investigated redox potentials favourable for donating electrons to dissolved and insoluble components in Catalina Harbor marine sediment by combining electrochemical techniques with geochemistry and molecular methods. Working electrodes buried in sediment microcosms were poised at seven redox potentials between −300 and −750 mV versus Ag/AgCl using a three‐electrode system. In electrode biofilms recovered after 2‐month incubations, overall community diversity increased with more negative redox potentials. Abundances of known EET‐capable groups (e.g., Alteromonadales and Desulfuromonadales ) varied with redox potential. Motility and chemotaxis genes were found in greater abundance in electrode communities, suggesting a possible selective advantage of these pathways for colonization and utilization of the electrode. Our enrichments demonstrated the validity of this approach in capturing groups known, as well as novel groups (e.g., Campylobacterales ) that perform EET. The diverse nature of the enriched cathode communities suggest that insoluble substrate oxidation may be a critical, although poorly described microbial metabolic process in marine sediment.

An approach to hydrogeological modeling of a large system of groundwater-fed lakes and wetlands in the Nebraska Sand Hills, USA - Nathan R. Rossman; Vitaly A. Zlotnik; Clinton M. Rowe (Hydrogeology Journal, 2018)

Incorporating linear programing and life cycle thinking into environmental sustainability decision-making: a case study on anchovy canning industry - I. Garcia-Herrero; J. Laso; M. Margallo; A. Bala; C. Gazulla; P. Fullana-i-Palmer; I. Vázquez-Rowe; A. Irabien; R. Aldaco (Clean Technologies and Environmental Policy, 2017)

In situ electrochemical enrichment and isolation of a magnetite‐reducing bacterium from a high pH serpentinizing spring - Annette R. Rowe; Miho Yoshimura; Doug E. LaRowe; Lina J. Bird; Jan P. Amend; Kazuhito Hashimoto; Kenneth H. Nealson; Akihiro Okamoto (Environmental Microbiology, 2017)
Summary Serpentinization is a geologic process that produces highly reduced, hydrogen‐rich fluids that support microbial communities under high pH conditions. We investigated the activity of microbes capable of extracellular electron transfer in a terrestrial serpentinizing system known as ‘The Cedars’. Measuring current generation with an on‐site two‐electrode system, we observed daily oscillations in current with the current maxima and minima occurring during daylight hours. Distinct members of the microbial community were enriched. Current generation in lab‐scale electrochemical reactors did not oscillate, but was correlated with carbohydrate amendment in Cedars‐specific minimal media. Gammaproteobacteria and Firmicutes were consistently enriched from lab electrochemical systems on δ‐MnO 2 and amorphous Fe(OH) 3 at pH 11. However, isolation of an electrogenic strain proved difficult as transfer cultures failed to grow after multiple rounds of media transfer. Lowering the bulk pH in the media allowed us to isolate a Firmicutes strain ( Paenibacillus sp .). This strain was capable of electrode and mineral reduction (including magnetite) at pH 9. This report provides evidence of the in situ activity of microbes using extracellular substrates as sinks for electrons at The Cedars, but also highlights the potential importance of community dynamics for supporting microbial life through either carbon fixation, and/or moderating pH stress.

Application of novel analytical ultracentrifuge analysis to solutions of fungal mannans - Richard B. Gillis; Gary G. Adams; David T. M. Besong; Eva Machová; Anna Ebringerová; Arthur J. Rowe; Stephen E. Harding; Trushar R. Patel (European Biophysics Journal, 2017)

Nestedness and species replacement along bathymetric gradients in the deep sea reflect productivity: a test with polychaete assemblages in the oligotrophic north‐west Gulf of Mexico - Carol T. Stuart; Solange Brault; Gilbert T. Rowe; Chih‐Lin Wei; Martine Wagstaff; Craig R. McClain; Michael A. Rex (Journal of Biogeography, 2017)
Aim To test the hypothesis that low productivity drives the nestedness component of β‐diversity in polychaetes at the deep‐sea floor. Location Western Gulf of Mexico. Methods We used A. Baselga's (2010, Global Ecology and Biogeography, 19 , 134–143) metrics of species replacement and nestedness to assess their overall significance with differences in depth and particulate organic carbon ( POC ) flux to the seafloor. We used M. A. Rodríguez‐Gironés & L. Santamaría's (2006, Journal of Biogeography , 33 , 924–935) BINMATNEST to calculate the significance and direction of nestedness with depth and POC flux. Results Nestedness was the most significant part of β‐diversity with depth and POC flux. The rank order of nestedness increased significantly with increasing depth, and decreased significantly with increasing POC flux. There was little endemism below 2000 m. Main conclusion The polychaete fauna in the deepest western Gulf of Mexico is largely a nested subset of the shallower upper to mid‐bathyal fauna. While the causes of β‐diversity in the deep sea are undoubtedly multivariate, the relative importance of turnover and nestedness appears to be modulated by productivity in the form of POC flux to the seafloor. Under circumstances of extremely low POC flux and animal density in the deepest reaches of the Gulf, nestedness may be caused by some populations being maintained by immigration from larger populations upslope, or by biogeographic filtering for tolerance to abyssal conditions. Resources at great depths in regions of exceptionally low productivity may be too limited to permit adaptation resulting in endemism and continued downslope turnover. If productivity helps to explain the nestedness part of β‐diversity, this may lead to a more unified theory of deep‐sea biodiversity.

Mechanistic evaluation of primary human hepatocyte culture using global proteomic analysis reveals a selective dedifferentiation profile - James A. Heslop; Cliff Rowe; Joanne Walsh; Rowena Sison-Young; Roz Jenkins; Laleh Kamalian; Richard Kia; David Hay; Robert P. Jones; Hassan Z. Malik; Stephen Fenwick; Amy E. Chadwick; et al. (Archives of Toxicology, 2017)

Expanding the concept of sustainable seafood using Life Cycle Assessment - Friederike Ziegler; Sara Hornborg; Bridget S Green; Ole Ritzau Eigaard; Anna K Farmery; Linus Hammar; Klaas Hartmann; Sverker Molander; Robert W R Parker; Erik Skontorp Hognes; Ian Vázquez‐Rowe; Anthony D M Smith (Fish and Fisheries, 2016)
Fisheries management and sustainability assessment of fisheries more generally have recently expanded their scope from single‐species stock assessment to ecosystem‐based approaches, aiming to incorporate economic, social and local environmental impacts, while still excluding global‐scale environmental impacts. In parallel, Life Cycle Assessment ( LCA ) has emerged as a widely used and recommended framework to assess environmental impacts of products, including global‐scale impacts. For over a decade, LCA has been applied to seafood supply chains, leading to new insights into the environmental impact of seafood products. We present insights from seafood LCA research with particular focus on evaluating fisheries management, which strongly influences the environmental impact of seafood products. Further, we suggest tangible ways in which LCA could be taken up in management. By identifying trade‐offs, LCA can be a useful decision support tool and avoids problem shifting from one concern (or activity) to another. The integrated, product‐based and quantitative perspective brought by LCA could complement existing tools. One example is to follow up fuel use of fishing, as the production and combustion of fuel used dominates overall results for various types of environmental impacts of seafood products, and is also often linked to biological impacts of fishing. Reducing the fuel use of fisheries is therefore effective to reduce overall impacts. Allocating fishing rights based on environmental performance could likewise facilitate the transition to low‐impact fisheries. Taking these steps in an open dialogue between fishers, managers, industry, NGO s and consumers would enable more targeted progress towards sustainable fisheries.

Depth and temperature associations of haddock Melanogrammus aeglefinus off southern Newfoundland - R. Rogers; S. Rowe; M. J. Morgan (Journal of Fish Biology, 2016)
Using data collected as part of offshore surveys conducted during 1972–2013, haddock Melanogrammus aeglefinus association patterns with depth and temperature in southern Newfoundland waters, the northern extremity of the species' range in the western Atlantic Ocean, were quantified. They were typically concentrated in the deep warm waters along the narrow shelf slope in North‐west Atlantic Fisheries Organization Divisions 3O and 3P with individuals moving seasonally into the shallow waters of the banks as they warmed. While M. aeglefinus were found over a range of depths and temperatures, they were primarily located at depths deeper and temperatures warmer than the median sampled. Analyses demonstrated that of the two hydrographic variables assessed, temperature was most influential in structuring distribution, with individuals appearing to change depth in order to maintain similar temperature throughout the year. Melanogrammus aeglefinus were found predominantly in temperatures of c. 4–8° C which often represented some of the warmest waters available. Differences in fish‐habitat association patterns in relation to sex or maturity status were not readily apparent from the analyses. Warming conditions off Newfoundland and Labrador in recent years might be predicted to improve local M. aeglefinus productivity.

Risk/Benefit Communication about Food—A Systematic Review of the Literature - L. J. Frewer; A. R. H. Fischer; M. Brennan; D. Bánáti; R. Lion; R. M. Meertens; G. Rowe; M. Siegrist; W. Verbeke; C. M. J. L. Vereijken (Critical Reviews in Food Science and Nutrition, 2016)

Terrestrial runoff boosts phytoplankton in a Mediterranean coastal lagoon, but these effects do not propagate to higher trophic levels - A. Liess; O. Rowe; S. N. Francoeur; J. Guo; K. Lange; A. Schröder; B. Reichstein; R. Lefèbure; A. Deininger; P. Mathisen; C. L. Faithfull (Hydrobiologia, 2016)

Scale effects on the pattern and predictors of small mammal diversity along a local elevational gradient in the Great Basin - Rebecca J. Rowe; Lawrence R. Heaney; Eric A. Rickart (Journal of Biogeography, 2015)
Aim Evaluation of the generality of the diversity–elevation relationship has highlighted effects of scale (spatial extent and grain size) on pattern perception. In contrast, the effects of scale on the attribution of drivers of diversity along elevational gradients remain largely unexplored. This is important because many causal factors have been proposed, and remotely sensed data about abiotic factors are available at increasingly fine grain sizes. Here, we evaluate the effects both of the resolution of the species diversity estimate on the pattern perceived, and of environmental predictor grain size on the potential contribution to each pattern. Location Ruby Mountains, Nevada, western North America. Methods For the small mammal fauna along one local elevational gradient, we compared patterns among estimates of richness derived from site‐based occurrences rarefied by survey effort and those inferred from interpolation across species’ elevational ranges. Using an information‐theoretic approach, we evaluated the relative importance of spatial and environmental factors in structuring each richness distribution. Climate and habitat were assessed at coarse and fine grain sizes. Comparisons were based on model fit and relative variable importance. Results We find general congruence in the diversity–elevation relationship, with peak diversity near the midpoint of the sampled gradient. Despite this commonality in pattern, we find the attribution of underlying drivers is substantially influenced by the type of richness estimate and by the grain size of the predictor variables. Main conclusions Our results illustrate that the factors identified as predictors of diversity can be sensitive to grain size, and that this sensitivity is not equally apparent under different measures of richness obtained from the same survey data. We call for broader discussion of scale effects and resolution appropriateness for elevational diversity gradients. This is particularly important because mismatches in scale may result in misguided conservation or management initiatives.

Terrestrial runoff may reduce microbenthic net community productivity by increasing turbidity: a Mediterranean coastal lagoon mesocosm experiment - A. Liess; C. Faithfull; B. Reichstein; O. Rowe; J. Guo; R. Pete; G. Thomsson; W. Uszko; S. N. Francoeur (Hydrobiologia, 2015)

High influx of carbon in walls of agglutinated foraminifers during the Permian–Triassic transition in global oceans - Galina P. Nestell; Merlynd K. Nestell; Brooks B. Ellwood; Bruce R. Wardlaw; Asish R. Basu; Nilotpal Ghosh; Luu Thi Phuong Lan; Harry D. Rowe; Andrew Hunt; Jonathan H. Tomkin; Kenneth T. Ratcliffe (International Geology Review, 2015)

Testing a post-copulatory pre-zygotic reproductive barrier in a passerine species pair - Emily R. A. Cramer; Terje Laskemoen; Fabrice Eroukhmanoff; Fredrik Haas; Jo S. Hermansen; Jan T. Lifjeld; Melissah Rowe; Glenn-Peter Sætre; Arild Johnsen (Behavioral Ecology and Sociobiology, 2014)

TESS Ad-Mixer: A novel program for visualizing TESS Q matrices - Matthew W. Mitchell; Brian Rowe; Paul R. Sesink Clee; Mary Katherine Gonder (Conservation Genetics Resources, 2013)

Cue integration and the perception of action in intentional binding - Noham Wolpe; Patrick Haggard; Hartwig R. Siebner; James B. Rowe (Experimental Brain Research, 2013)

Recent advances in 2D and 3D in vitro systems using primary hepatocytes, alternative hepatocyte sources and non-parenchymal liver cells and their use in investigating mechanisms of hepatotoxicity, cell signaling and ADME - Patricio Godoy; Nicola J. Hewitt; Ute Albrecht; Melvin E. Andersen; Nariman Ansari; Sudin Bhattacharya; Johannes Georg Bode; Jennifer Bolleyn; Christoph Borner; Jan Böttger; Albert Braeuning; Robert A. Budinsky; et al. (Archives of Toxicology, 2013)

Presence, genetic variability, and potential significance of “Candidatus Midichloria mitochondrii” in the lone star tick Amblyomma americanum - Amanda Jo Williams-Newkirk; Lori A. Rowe; Tonya R. Mixson-Hayden; Gregory A. Dasch (Experimental and Applied Acarology, 2012)

CCL20 Is Associated with Neurodegeneration Following Experimental Traumatic Brain Injury and Promotes Cellular Toxicity In Vitro - Christopher C. Leonardo; James Musso; Mahasweta Das; Derrick D. Rowe; Lisa A. Collier; Shyam Mohapatra; Keith R. Pennypacker (Translational Stroke Research, 2012)

High rate of prey consumption in a small predatory fish on coral reefs - W. E. Feeney; O. M. Lönnstedt; Y. Bosiger; J. Martin; G. P. Jones; R. J. Rowe; M. I. McCormick (Coral Reefs, 2012)

The spleen contributes to stroke induced neurodegeneration through interferon gamma signaling - Hilary A. Seifert; Christopher C. Leonardo; Aaron A. Hall; Derrick D. Rowe; Lisa A. Collier; Stanley A. Benkovic; Alison E. Willing; Keith R. Pennypacker (Metabolic Brain Disease, 2012)

Quantification of total and particulate dimethylsulfoniopropionate (DMSP) in five Bermudian coral species across a depth gradient - D. M. Yost; R. Jones; C. L. Rowe; Carys Louise Mitchelmore (Coral Reefs, 2012)

Impacts of atmospheric nitrogen deposition: responses of multiple plant and soil parameters across contrasting ecosystems in long‐term field experiments - Gareth K. Phoenix; Bridget A. Emmett; Andrea J. Britton; Simon J. M. Caporn; Nancy B. Dise; Rachel Helliwell; Laurence Jones; Jonathan R. Leake; Ian D. Leith; Lucy J. Sheppard; Alwyn Sowerby; Michael G. Pilkington; et al. (Global Change Biology, 2012)
Atmospheric nitrogen ( N ) deposition is a global and increasing threat to biodiversity and ecosystem function. Much of our current understanding of N deposition impacts comes from field manipulation studies, although interpretation may need caution where simulations of N deposition (in terms of dose, application rate and N form) have limited realism. Here, we review responses to simulated N deposition from the UKREATE network, a group of nine experimental sites across the UK in a diversity of heathland, grassland, bog and dune ecosystems which include studies with a high level of realism and where many are also the longest running globally on their ecosystem type. Clear responses were seen across the sites with the greatest sensitivity shown in cover and species richness of bryophytes and lichens. Productivity was also increased at sites where N was the limiting nutrient, while flowering also showed high sensitivity, with increases and declines seen in dominant shrub and forb species, respectively. Critically, these parameters were responsive to some of the lowest additional loadings of N (7.7–10 kg ha −1 yr −1 ) showing potential for impacts by deposition rates seen in even remote and ‘unpolluted’ regions of E urope. Other parameters were less sensitive, but nevertheless showed response to higher doses. These included increases in soil % N and ‘plant available’ KCl extractable N , N cycling rates and acid–base status. Furthermore, an analysis of accumulated dose that quantified response against the total N input over time suggested that N impacts can ‘build up’ within an ecosystem such that even relatively low N deposition rates can result in ecological responses if continued for long enough. Given the responses have important implications for ecosystem structure, function, and recovery from N loading, the clear evidence for impacts at relatively low N deposition rates across a wide range of habitats is of considerable concern.

Stress-induced reinstatement of alcohol-seeking in rats is selectively suppressed by the neurokinin 1 (NK1) antagonist L822429 - Jesse R. Schank; Charles L. Pickens; Kelly E. Rowe; Kejun Cheng; Annika Thorsell; Kenner C. Rice; Yavin Shaham; Markus Heilig (Psychopharmacology, 2011)

Structure and heterogeneity of gliadin: a hydrodynamic evaluation - Shirley Ang; Jana Kogulanathan; Gordon A. Morris; M. Samil Kök; Peter R. Shewry; Arthur S. Tatham; Gary G. Adams; Arthur J. Rowe; Stephen E. Harding (European Biophysics Journal, 2010)

Amyloid Imaging in Alzheimer’s Disease and Other Dementias - Michelle T. Fodero-Tavoletti; Roberto Cappai; Catriona A. McLean; Kerryn E. Pike; Paul A. Adlard; Tiffany Cowie; Andrea R. Connor; Colin L. Masters; Christopher C. Rowe; Victor L. Villemagne (Brain Imaging and Behavior, 2009)

Galantamine-induced improvements in cognitive function are not related to alterations in α4β2 nicotinic receptors in early Alzheimer’s disease as measured in vivo by 2-[18F]Fluoro-A-85380 PET - J. R. Ellis; P. J. Nathan; V. L. Villemagne; R. S. Mulligan; T. Saunder; K. Young; C. L. Smith; J. Welch; M. Woodward; K. A. Wesnes; G. Savage; C. C. Rowe (Psychopharmacology, 2009)

Dispersal, disturbance and the contrasting biogeographies of New Zealand’s diadromous and non‐diadromous fish species - J. R. Leathwick; J. Elith; W. L. Chadderton; D. Rowe; T. Hastie (Journal of Biogeography, 2008)
Aim To examine the relationship between diadromy and dispersal ability in New Zealand’s freshwater fish fauna, and how this affects the current environmental and geographic distributions of both diadromous and non‐diadromous species. Location New Zealand. Methods Capture data for 15 diadromous and 15 non‐diadromous fish species from 13,369 sites throughout New Zealand were analysed to establish features of their geographic ranges. Statistical models were used to determine the main environmental correlates of species’ distributions, and to establish the environmental conditions preferred by each species. Environmental predictors, chosen for their functional relevance, were derived from an extensive GIS database describing New Zealand’s river and stream network. Results In terms of geography, most diadromous species occur in a scattered fashion throughout extensive geographic ranges, and occupy large numbers of catchments of widely varying size. By contrast, most non‐diadromous species show relatively high levels of occupancy of smaller geographic ranges, and most are restricted to a few large catchments, particularly in the eastern South Island. In terms of environment, there is marked separation of diadromous from non‐diadromous species, with diadromous species generally caught most frequently in low‐gradient coastal rivers and streams with warm, maritime climates. With a few notable exceptions, most diadromous species have lower occurrence in river segments that are located above obstacles to upstream migration. Non‐diadromous species are usually caught in inland rivers and streams with cool, strongly seasonal climates, typified by a low frequency of high‐intensity rainfall events. Main conclusions We interpret the contrasting biogeographies of New Zealand’s diadromous and non‐diadromous species as reflecting interaction between their marked differences in dispersal ability and a landscape that is subject to recurrent, often large‐scale, natural disturbance. While both groups are likely to be equally susceptible to local, disturbance‐driven extinction, the much greater dispersal ability of diadromous species has allowed them to persist over wide geographic ranges. By contrast, the distributions of most non‐diadromous species are concentrated in a few large catchments, mostly in regions where less intense natural disturbance regimes are likely to have favoured their survival.

Changes in fire regimes since the Last Glacial Maximum: an assessment based on a global synthesis and analysis of charcoal data - M. J. Power; J. Marlon; N. Ortiz; P. J. Bartlein; S. P. Harrison; F. E. Mayle; A. Ballouche; R. H. W. Bradshaw; C. Carcaillet; C. Cordova; S. Mooney; P. I. Moreno; et al. (Climate Dynamics, 2008)

Vegetation Type Affects the Relationship Between Soil Carbon to Nitrogen Ratio and Nitrogen Leaching - E. C. Rowe; C. D. Evans; B. A. Emmett; B. Reynolds; R. C. Helliwell; M. C. Coull; C. J. Curtis (Water, Air, & Soil Pollution, 2006)

The 14-year Performance of a Compacted Clay Liner used as Part of a Composite Liner System for a Leachate Lagoon - Craig B. Lake; R. Kerry Rowe (Geotechnical and Geological Engineering, 2005)

Hydrologic-energy balance constraints on the Holocene lake-level history of lake Titicaca, South America - H. D. Rowe; R. B. Dunbar (Climate Dynamics, 2004)

Genetic variability and heritability estimates for hardseededness and flowering in balansa clover (Trifolium michelianum Savi) populations - Ramakrishnan M. Nair; Andy D. Craig; Trevor D. Rowe; Steve R. Biggins; Colleen H. Hunt (Euphytica, 2004)

Optimal mechanisms for finding and selecting mates: how threespine stickleback ( Gasterosteus aculeatus ) should encode male throat colors - M. P. Rowe; C. L. Baube; E. R. Loew; J. B. Phillips (Journal of Comparative Physiology A, 2004)

Seasonal profiles in growth, energy reserves, gonad development, and plasma steroids in age 1+ cultured Chinook salmon (Oncorhynchus tshawytscha) females - M. J. Unwin; C. W. Poortenaar; D. K. Rowe; N. C. Boustead; M. J. R. Porter (New Zealand Journal of Marine and Freshwater Research, 2004)
Sexual maturation in 2‐year‐old female Chinook salmon (Oncorhynchus tshawytscha) is unknown within their native range, but occurs in up to 20% of farmed stocks in New Zealand. To characterise the seasonal timing of oogenesis and subsequent ovarian development, we measured levels of plasma 17β‐estradiol and testosterone, condition factor, and gonadosomatic and hepatosomatic index, for freshwater‐reared female Chinook at 2–4‐week intervals during their second year of life (May 2001‐April 2002). These comprised two treatment groups under additional 24 h illumination from September to January, and two ambient controls. Macroscopic ovarian development first occurred in mid September (8 months before spawning), coinciding with detectable increases (≥0.3 ng ml ‐1 ) in both plasma steroids. Vitellogenesis was first observed in November and coincided with an increase in hepatosomatic index, possibly indicating the liver's role in transferring lipids to the developing ova. Neither mean weight nor the percentage of maturating fish (mean 6.9%) differed between the treatment and control groups at the end of the experiment, but ovarian development in the treatment group was advanced by 13 days relative to the controls. Reduced dark phase plasma melatonin levels confirmed that the additional light was sufficiently intense to produce a physiological response in the artificially illuminated fish.

Antipredator responses of California ground squirrels to rattlesnakes and rattling sounds: the roles of sex, reproductive parity, and offspring age in assessment and decision-making rules - Ronald R. Swaisgood; Matthew P. Rowe; Donald H. Owings (Behavioral Ecology and Sociobiology, 2004)

Antipredator responses of California ground squirrels to rattlesnakes and rattling sounds: the roles of sex, reproductive parity, and offspring age in assessment and decision-making rules - Ronald R. Swaisgood; Matthew P. Rowe; Donald H. Owings (Behavioral Ecology and Sociobiology, 2003)

Predicting Biogeochemical Calcium Precipitation in Landfill Leachate Collection Systems - Jamie F. VanGulck; R. Kerry Rowe; Bruce E. Rittmann; Andrew J. Cooke (Biodegradation, 2003)

Increased Efficiency of Transgenic Livestock Production - Elizabeth A. Maga; R. Geoffrey Sargent; Hong Zeng; Sushma Pati; David A. Zarling; Stefanie M. Oppenheim; Nicole M.B. Collette; Alice L. Moyer; Janice S. Conrad-Brink; Joan D. Rowe; Robert H. BonDurant; Gary B. Anderson; et al. (Transgenic Research, 2003)

Depth Distribution and Abundance of the Common Bully, Gobiomorphus cotidianus (Eleotridae), in Three Oligotrophic New Zealand Lakes, One of which is Turbid - David K. Rowe; Shirley Nichols; Greg R. Kelly (Environmental Biology of Fishes, 2001)

Accumulation and Selective Maternal Transfer of Contaminants in the Turtle Trachemys scripta Associated with Coal Ash Deposition - R. D. Nagle, C. L. Rowe, J. D. Congdon (Archives of Environmental Contamination and Toxicology, 2001)

Failed Recruitment of Southern Toads ( Bufo terrestris ) in a Trace Element-Contaminated Breeding Habitat: Direct and Indirect Effects That May Lead to a Local Population Sink - C. L. Rowe, W. A. Hopkins, V. R. Coffm (Archives of Environmental Contamination and Toxicology, 2001)

A brief view of known landmarks reorientates path integration in hamsters - A. S. Etienne; V. Boulens; R. Maurer; T. Rowe; C. Siegrist (The Science of Nature, 2000)

Recovery ofVerticillium dahliae from North American certified seed potatoes and characterization of strains by vegetative compatibility and aggressiveness - M. A. Omer; D. A. Johnson; R. C. Rowe (American Journal of Potato Research, 2000)

Considerations on the use of video playbacks as visual stimuli: the Lisbon workshop consensus - R. F. Oliveira; G. G. Rosenthal; I. Schlupp; P. K. McGregor; I. C. Cuthill; J. A. Endler; L. J. Fleishman; J. Zeil; E. Barata; F. Burford; D. Gonçalves; M. Haley; et al. (acta ethologica, 2000)

Isotopic composition of xenon in petroleum from the shell bullwinkle field - J. Nuzzo; M. Hyman; M. W. Rowe; M. N. Rao; R. L. Palma; J. Westrich (Journal of Earth System Science, 2000)

Acute and Genotoxic Effects of Baku Harbor Sediment on Russian Sturgeon, Acipenser guildensteidti - J. W. Bickham; G. T. Rowe; G. Palatnikov; A. Mekhtiev; M. Mekhtiev; R. Y. Kasimov; D. W. Hauschultz; J. K. Wickliffe; W. J. Rogers (Bulletin of Environmental Contamination and Toxicology, 1998)

Snr , New Genetic Loci Common to the Nitrate Reduction Systems of Pseudomonas aeruginosa PAO1 - Vida R. Irani; Al. Darzins; John J. Rowe (Current Microbiology, 1997)

Resistance exercise training and the orthostatic response - John P. McCarthy; Marcas M. Bamman; Janice M. Yelle; Adrian D. LeBlanc; Roger M. Rowe; Michael C. Greenisen; Stuart M. C. Lee; Elisabeth R. Spector; Suzanne M. Fortney (European Journal of Applied Physiology, 1997)

Further analysis of the role of spectrin repeat motifs in α-actinin dimer formation - G. Flood; A. J. Rowe; D. R. Critchley; W. B. Gratzer (European Biophysics Journal, 1997)

Migration between nests in the Australian arid‐zone ant Rhytidoponera sp. 12 revealed by DGGE analyses of mitochondrial DNA - W. Tek Tay; J. M. Cook; D. J. Rowe; R. H. Crozier (Molecular Ecology, 1997)
Denaturing gradient gel electrophoresis (DGGE) of a PCR‐amplified region of the mitochondrial DNA (mtDNA) including a large part of the cytochrome b gene revealed four haplotypes among worker ants from 75 colonies of the queenless ant Rhytidoponera sp. 12. The DGGE results were checked by sequencing examples of the haplotypes; all changes were transitions and two haplotypes differed by only a single substitution. Previous work (e.g. Crozier et al. 1984) showed that intranest relatedness is low for nuclear genes yet neighbouring nests are related; gene flow via winged males appeared the best explanation for this phenomenon. Two mtDNA haplotypes were found in 34.7% of the colonies studied, showing that female movement also occurs between nests. Migration of mated individuals on such a large scale when the number of reproductives is relatively small is unexpected (Crozier & Pamilo 1996). An observed tendency to clumping of the haplotypes is in accordance with the wingless nature of the female dispersers.

Influence of cultivar resistance toVerticillium SPP. On potato early dying - T. A. Wheeler; R. C. Rowe; R. M. Riedel; L. V. Madden (American Journal of Potato Research, 1994)

Seasonal variation and effects of wheat rotation on populations ofVerticillium dahliae Kleb. in Ohio potato field soils - T. R. Joaquim; V. L. Smith; R. C. Rowe (American Journal of Potato Research, 1988)

Chromatographic studies on the origin of the cultivated diploid potatosolanum × ajanhuiri juz. et buk - Z. Huamán; J. G. Hawkes; P. R. Rowe (American Journal of Potato Research, 1983)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

Relationship of foliar ozone injury to maturity classification and yield of potatoes - A. R. Mosley; R. C. Rowe; T. C. Weidensaul (American Journal of Potato Research, 1978)

The accumulation and loss of dieldrin and endrin in the Eastern oyster - J. W. Mason; D. R. Rowe (Archives of Environmental Contamination and Toxicology, 1976)

s 60th annual PAA meeting (Part II) - J. Landeo; P. R. Rowe; M. Mayer de Scurrah; M. T. Jackson; P. R. Rowe; J. G. Hawkes; P. Jatala; H. A. Mendoza; F. L. Haynes; G. C. C. Tai; H. Dejong; N. S. Wright; et al. (American Journal of Potato Research, 1976)

s 60th annual meeting The Potato Association of America - R. Kunkel; N. M. Holstad; R. E. Thornton; J. C. Bishop; Herman Timm; V. C. Shekhar; W. M. Iritani; Thornton Robert; Gary Hyde; Malamud Oscar; Robert B. O’Keefe; Mccown Brent; et al. (American Journal of Potato Research, 1976)

s 59th annual meeting Potato Association of America - D. E. Hudson; M. D. Volz; B. B. DePhillips; Gene A. Mathia; Frank Haynes; N. A. Wynn; Allen E. Abrahams; Lewis A. Schaper; Paul H. Orr; Earl C. Yaeger; Combs Joseph; Robert L. Mercer; et al. (American Journal of Potato Research, 1975)

Disomic inheritance of anthocyanins and flavonol glycosides in the Tetraploid tuber-bearing speciesSolanum stoloniferum - E. R. Everhart; P. R. Rowe (American Journal of Potato Research, 1974)

A root inoculation technique to screen potato seedlings for resistance toPseudomonas solanacearum - Luis C. Gonzalez; Luis Sequeira; P. R. Rowe (American Journal of Potato Research, 1973)

The dimensions of existingSolanum germ plasma collections - P. R. Rowe (American Journal of Potato Research, 1970)

Selection and utilization of solanum phureja clones with high resistance to different strains of pseudomonas solanacearum - Luis Sequeira; P. R. Rowe (American Journal of Potato Research, 1969)

The Potatoes of Argentina, Brazil, Paraguay and Uruguay. By J. G. Hawkes and J. P. Hjerting - P. R. Rowe (American Journal of Potato Research, 1969)

Quantitative variation in diploid potatoes - P. R. Rowe (American Journal of Potato Research, 1969)

Utilizing the frost resistance of diploid solanum species - R. W. Ross; P. R. Rowe (American Journal of Potato Research, 1969)

Performance and variability of diploid and tetraploid potato families - P. R. Rowe (American Journal of Potato Research, 1967)

Performance of diploid and vegetatively doubled clones of Phureja-haploid tuberosum hybrids - P. R. Rowe (American Journal of Potato Research, 1967)

The United States potato collection - P. R. Rowe (American Journal of Potato Research, 1966)

Frost resistance among theSolanum species in the ir-1 potato collection - R. W. Ross; P. R. Rowe (American Journal of Potato Research, 1965)